The evaluation of the treatment for old osteoporotic vertebral compression fracture pain by percutaneous vertebroplasty. Issue 27 (2nd July 2020) - Zhao, Peng; Guo, Aifeng; Tan, Zhongjiang; Li, Tianqiang; Zhao, Fei; Li, Jie; Yan, Wenliang
Abstract : Abstract: The aim of the present study was to evaluate the clinical effect of percutaneous vertebroplasty (PVP) in the treatment of old osteoporotic vertebral compression fracture (OVCF) pain. A retrospective study was conducted on the clinical and imaging data of 31 patients with old OVCF treated by PVP from June 2010 to September 2011. Clinical efficacy was evaluated by the visual analog scale (VAS) scores, the oswestry disability index (ODI), the Cobb angle, and vertebral kyphotic angle at pre-operation and post-operation 3 days, 3 months, and 12 months. The VAS scores and ODI scores of 3 day, 3 month, and 12 month after PVP were significantly improved compared with those before operation ( P  < .05), but the Cobb angle and vertebral kyphosis angle were not significantly improved compared with those before operation ( P  > .05). PVP can effectively relieve the pain caused by old OVCF, and the motor ability of the patients is improved obviously. However, the recovery of Cobb angle and vertebral kyphosis angle was not obvious.